Sexually transmitted diseases prevention by university students: reflections in the light of Henssen's theory of knowledge (Research, Society and Development, 2021)
The objective was to reflect on the knowledge of young university students regarding the prevention of STIs, in the light of Johannes Henssen's theory of knowledge. It is a reflection article in which articles were searched for access online, in the months of December 2020 and January 2021, in the (inter) nationally indexed databases, as well as Henssen's works on General Theory of Knowledge. The results were discussed in two thematic blocks: 1) Knowledge as a factor for behavior change; 2) Knowledge of young university students on STI prevention. It is concluded, from the reflections presented, that the process of obtaining knowledge aims to equip people, like young university students, with cognitive resources that enable them to use methodical and competent reason and discernment about STIs, behaviors of health risk and preventive measures through the adoption of safe sexual practices. It was identified that, although knowledge is of paramount importance in this context, it does not figure as the sole and main guide for young people's practices and behaviors, which suggests the need for studies that evaluate the factors associated with the behaviors adopted by the group.